Tesla: New Leader of Wworld “Boom” of Sales of Electric Vehicles or New “Exchange Bubble”? - Andrei I. Sosnilo; Anastasia V. Kunashko (Управленческое консультирование)
The article considers modern trends in the development of the automotive market and, in particular, the segment of electric vehicles. The data on the number of cars per 1000 population has been analyzes, as well as the volume of car sales in 2016-2017. The analysis reveals the share of electric vehicles in the total amount of new cars sales. Authors studied the dynamics of changes in sales of electric vehicles in the markets of developed countries and calculated the annual change in indicators in percent. The governmental plans of leading countries for electric vehicles have been described and the sales volumes of the most popular models of electric vehicles have been analyzed. Authors evaluated the performance of Tesla and revealed an increase in debts. Particularly, there is no dividend payouts per share. Authors identified the reasons for the growth in the value of companies, and concluded that the value of the Tesla’s shares was over-valued.